2023
DOI: 10.1007/s00296-023-05319-0
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID in autoimmune rheumatic diseases

Abstract: Consequences of Corona Virus Disease-19 (COVID-19) in patients with rheumatic diseases (RDs) are clinically diverse. SARS-CoV-2 infection has been associated with various autoimmune and rheumatic manifestations over the past three years. Emerging evidence points to the possibility of Long COVID predisposition in rheumatic patients due to the changes in immune regulatory response. The aim of this article was to overview data on the pathobiology of Long COVID in patients with RDs. Related risk factors, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…There is currently ample evidence that autoimmunity and immune hypofunction play an important role in many patients with long COVID. [50][51][52][53] This includes not only the occurrence of Multisystem Inflammatory Syndrome in Children [54] but also an increase in incidence of common infections such as respiratory syncytial virus (RSV) and streptococcal disease.…”
Section: Immune Hypofunction After Acute Covid-19mentioning
confidence: 99%
“…There is currently ample evidence that autoimmunity and immune hypofunction play an important role in many patients with long COVID. [50][51][52][53] This includes not only the occurrence of Multisystem Inflammatory Syndrome in Children [54] but also an increase in incidence of common infections such as respiratory syncytial virus (RSV) and streptococcal disease.…”
Section: Immune Hypofunction After Acute Covid-19mentioning
confidence: 99%
“…The emergence of the SARS‐CoV‐2 virus, which causes COVID‐19, has been associated with the production of various autoantibodies including antinuclear antibodies (ANA), anti‐Ro/Sjögren's syndrome A antibodies, and antiphospholipid antibodies. These autoantibodies have been observed in 11% to 53.6% of people in the acute phase of the disease, with a higher frequency in critically ill COVID‐19 patients 2–6 . Moreover, high ANA titers were found in 43.6% of patients at 12 months post‐COVID‐19 symptom onset 7 .…”
Section: Figurementioning
confidence: 99%
“…Distinguishing between the new onset of SLE and COVID‐19 or the so‐called “long COVID” can be challenging due to the shared characteristics between the two conditions. For instance, arthritis and musculoskeletal symptoms are present in over 85% of SLE patients and 65% of persons with “long COVID” 2 years after contracting SARS‐CoV‐2 6,11 . Therefore, analyzing cases of SLE with a temporal association with SARS‐CoV‐2 infection is crucial for identifying clinical clues that can aid in differentiating these 2 conditions.…”
Section: Figurementioning
confidence: 99%
“…It has been reported that patients with ARDs have higher rates of SARS-CoV-2 infection and an increased mortality rate ( 9 ). In addition, patients with ARDs often experience severe complications after infection due to immune imbalance, which can result in multiple organ damage ( 10 ). Moreover, COVID-19 might a risk factor for rheumatic disease relapse ( 11 ).…”
Section: Introductionmentioning
confidence: 99%